Publishing in hematology journals: A Scientometric and economic evaluation - TOPTAŞ, TAYFUR (My University, 2020)
Introduction: Herein, we aimed to compare the scientometric data of hematology journals, and compare the publication models, especially the scientometric data of journals with all-open access (OA) and hybrid-OA publication models.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; hematology; health scientometrics; scientometrics; open access publishing; economics; open access; EIGENFACTOR SCORE; RANK INDICATOR; IMPACT FACTOR; PUBLICATION FEES